Adesivos estruturais como alternativa para uniões mecânicas : análise e validação - Ribeiro, João Henrique da Silva (2022)
To carry out alterations in areas with explosive atmospheres, it is not possible to use processes with termal energy generation or the use of conventional electric tools, in this way this research seeks to validate the structural bonding of mechanical joints between new and existing structures in these spaces, seeking to bring an alternative solution for structural alterations in several sectors of the chemical industry. To achieve this objective, this works carries out a bibliographic study on all relevant topics for the application of structural adhesives in these joints, involving research on structural adhesives, as well as the loads generated in these applications, calculation models for these joints and possible limitations. The next point of the research was to carry out mechanical tests of adhesive joints, according to the relevant standards for each type of loading, in order to obtain the characteristics of the union generated by the selected adhesive. These data support points already expected, such as low value of mechanical strength for peeling, and also add application opportunities, such as high mechanical strength for traction, na effect that was not expected. Based on the data collected in tests, technical data and literature review, it was possible to perform numerical simulations in models of adhesive structures that represent practical applications of supports for pipes. In these simulations, the behavior under static loading of adhesive joints is analyzed, as well as the maximum load supported in a real application model, which was approximately 90 kN. On the other hand, the three models with static loading showed satisfactory results, where the tension found in the adhesive is significantly lower than the yield stress obtained in the tensile tests. In this way a better understading of the behavior of the material for the application becomes possible, the use of the method is also validated, with some restrictions, which are duly presented.